E-Government as Intervening of Work Culture To Increase Internal Customer Satisfaction - Frinaldi, Aldri; Embi, Muhamad Ali; Bila, Aziza; Urrahmi, Miftah (International Journal of Psychosocial Rehabilitation, 2020)
: Work culture change among employee in local governance organization have become concrete and important issues to discussed. Massive change in dynamic of life in various sector during industrial revolution era4.0 effected acceleration of information technology. It also effect to the way of work as an urgent matter. Acceleration of information technology must be accompanied by transformation of performance achievement based on digital governance. However, the implementation of digital governance is not parallel with adaptive work culture of employees in local governance organization that have been entrenched on the agency. As an effect, there are still many of governance work which grope technology. The objective of this paper was proved that implementation of digital governance can be carried out optimally when accompanied by adaptive work culture. This research used quantitative approach with survey strategy. The collected data was analyzed using T test, F test and path analysis. The result of study found that the work culture have direct and indirect effect toward employee satisfaction.